B.I.J.A.K buku idea jana kewangan / Nor Aizan Mohamed ... [et al.] - Mohamed, Nor Aizan; Ramli, Nur Alia Sabrina; Radzuan, Rabiatul Adawiyah; Adnan, Nurfardina Shafiqa; Mohd Nor, Mohamad Syazwan (Universiti Teknologi MARA, Kedah, 2023)
Nowadays, financial planning is important, but not everyone is aware of that, especially people who have visual impairment. It is because normal people can learn from the internet but people who have visual impairment often face various obstacles and find it hard to access inputs on financial planning. This condition is caused by the lack of financial awareness about OKU friendly products for the blind people. We realized that there are so few OKU friendly products in the market especially for people with disabilities. From this problem, we came out with a learning aid called B.I.J.A.K that stands for “Buku Idea Jana Kewangan”. It is a flash card made for people with visual impairment. It is a learning aid for basic financial planning to help people with visual impairments. This product will include theoretical questions on basic financial planning in the front of the card and the answer will be given at the back, just like any other flash card except for the fact that this flash card will be written with braille. Another reason for us to create this product is so that we could make learning financially possible for everyone including people with disabilities. Our target user is for the community from age 18 and above that is already working that wants to learn about financial planning who has visual impairment. Hopefully with our effort to create this product, we will be able to also raise awareness for companies to create more OKU friendly products.